2023
DOI: 10.1186/s40348-023-00163-5
|View full text |Cite
|
Sign up to set email alerts
|

Retinopathy of prematurity: from oxygen management to molecular manipulation

Jonathan Woods,
Susmito Biswas

Abstract: Introduction Retinopathy of prematurity (ROP) is a vasoproliferative disorder of the premature retina with the potential to progress to extraretinal neovascularisation. This review serves as an introduction to retinopathy of prematurity (ROP), outlining key parts of ROP pathophysiology, diagnosis and treatment. ROP is traditionally diagnosed by indirect ophthalmoscopy and classified using anatomical zones, stages of disease, and the presence or absence of “plus disease” (dilation and tortuosity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 78 publications
0
14
0
Order By: Relevance
“…Recent studies hypothesized that lower Insulin-like growth factor-1 (IGF-1) levels at birth could be related to the ROP occurrence, and infants' nutrition could alter the IGF-1 levels (19). In addition, a systematic review demonstrated a protective role for human milk intake against the ROP and its severe forms (20).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies hypothesized that lower Insulin-like growth factor-1 (IGF-1) levels at birth could be related to the ROP occurrence, and infants' nutrition could alter the IGF-1 levels (19). In addition, a systematic review demonstrated a protective role for human milk intake against the ROP and its severe forms (20).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies hypothesized that lower Insulin-like growth factor-1 (IGF-1) levels at birth could be related to the ROP occurrence, and infants’ nutrition could alter the IGF-1 levels [ 21 ]. In addition, a systematic review demonstrated a protective role for human milk intake against the ROP and its severe forms [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen plays a central role in retinal vessel development 4 , 5 . In utero, ‘physiological hypoxia’ allows normal retinal angiogenesis, primarily at the retinal periphery 6 , 7 , with VEGF playing a key role 8 .…”
Section: Introductionmentioning
confidence: 99%